'Everything is permitted': William Burroughs' Cut-up Novels and European Art. (1st September 2013) - Cran, Rona
Abstract : This essay suggests that during the 1960s William Burroughs was as much an avant-garde European artist as he was an American novelist. It argues that the nature of his cut-up novels requires readers to situate them within the context of twentieth-century European art — specifically collage — as well as American literature. Burroughs held the view that 'if writing is to have a future it must at least catch up with the past and learn to use techniques that have been used for some time past in painting'. This attitude towards his writing led him back into the rich, experimental half-century of European art which had gone before him, and into which his resulting cut-up work must be incorporated if its profoundly confusing and anacathartic effects upon readers are to be in any way tempered.